2006
DOI: 10.1007/s10750-005-1803-z
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Atmospheric Deposition Chemistry over the Alps: Present Status and Long-term Trends

Abstract: Several research programs monitoring atmospheric deposition have been launched in the Alpine countries in the last few decades. This paper uses data from previous and ongoing projects to: (i) investigate geographical variability in wet deposition chemistry over the Alps; (ii) assess temporal trends of the major chemical variables in response to changes in the atmospheric emission of pollutants; (iii) discuss the potential relationship between the status of atmospheric deposition and its effects on forest ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 54 publications
7
71
0
1
Order By: Relevance
“…Similar effects are found from rainout of air pollution from traffic and fossil fuel-based heating along the pre-Alps (39). In such areas, species loss may be found as a consequence of eutrophication, which would go along with a negative rather than positive biodiversity-productivity relationship due to competitive exclusion.…”
Section: Discussionmentioning
confidence: 64%
“…Similar effects are found from rainout of air pollution from traffic and fossil fuel-based heating along the pre-Alps (39). In such areas, species loss may be found as a consequence of eutrophication, which would go along with a negative rather than positive biodiversity-productivity relationship due to competitive exclusion.…”
Section: Discussionmentioning
confidence: 64%
“…5d) peaked at 4.2 mg N L -1 in the whole water mass soon after the liming; thereafter concentrations decreased steadily due to the dilution from the tributary waters, with their much lower concentrations (1.3-2.8 mg L -1 ). At present, in-lake values are close to 1 mg N L -1 , not far from those of the nearby Lake Maggiore, whose nitrogen levels are currently controlled largely by atmospheric input of nitrogen, both as ammonium and nitrate (Rogora et al, 2006a). The epilimnetic nitrate concentration in Lake Orta has regular seasonal variations, with minima in the spring and summer, due to biological activity and to the more intense effect of the tributary waters during the period of thermal stratification.…”
Section: The Recent Phase Of Recoverymentioning
confidence: 77%
“…This decrease has probably contributed to the decline in May to August NO 3 -N concentrations that we observed in the Swedish reference lakes since 1988. A decrease in atmospheric NO 3 -N deposition is not detectable everywhere in the Northern Hemisphere, the Alp region in Central Europe being an example (Rogora et al 2006). Lack of significant trends in atmospheric NO 3 -N deposition might be one of many explanations why, for instance, Evans et al (2001) and Skjelkvale et al (2005) found a variety of surface waters across the Northern Hemisphere without significant trends in NO 3 -N concentrations.…”
Section: Resultsmentioning
confidence: 99%